The Bryophyte Flora of Vienna - Harald G. Zechmeister; Michaela Kropik (Plants, 2023)
The bryophyte flora of Vienna is documented only in parts. Old finds often appeared in publications about Lower Austria; only one study addressed the bryophytes of the inner city. Here, we present a bryophyte flora of Vienna, including historical reports and the results of recent investigations. From 1998 to 2023, we recorded 329 bryophyte taxa in Viennese urban territory. Fifty-six of these were liverworts, and 273 were mosses. Sixty-seven taxa are new for Vienna. Forty-nine taxa, given in historical studies, could no longer be found. If we also count these, 378 taxa occurred in Vienna to date. Of the current occurring bryophytes, 67 species have an endangerment classification. Rich in bryophytes were the dry grasslands of the Lobau, the oxbow lakes of the Lobau and the Prater, and large parts of the Wienerwald. But flat roofs and inner-city areas also showed more than 100 species. Compared to other European cities, Vienna is decidedly species-rich and highly responsible for some species in Austria. Reasons for this are the extensive green spaces and the pronounced climatic gradient from the sub-oceanic west to the sub-continental east of Vienna. Awareness raising for bryophytes we recommend in addition to the existing biotope protection.